Leisure-time organised physical activity and dietary intake among Swedish adolescents. Issue 11 (3rd June 2022) - Fröberg, Andreas; Lindroos, Anna-Karin; Moraeus, Lotta; Patterson, Emma; Warensjö Lemming, Eva; Nyberg, Gisela
ABSTRACT: This study aimed to investigate associations between participation in leisure-time organised physical activity (LTOPA) and dietary intake in a large representative sample of Swedish adolescents participating in the national dietary survey Riksmaten Adolescents 2016–2017. A sample of 2807 participants aged 11–12, 14–15 and 17–18 years were included. Information about LTOPA and dietary intake were collected through questionnaires and two 24-hour recalls on the web (RiksmatenFlex). For dietary intake, overall healthy eating index, intake of fruit, vegetables, candy, sugar-sweetened beverages, and the proportion of added sugar to total energy intake were analysed. Significance-testing for associations was performed with analysis of covariance. LTOPA was associated with lower sugar-sweetened beverages intake among adolescent boys (p < 0.001, ηp2 = 0.012) and girls (p = 0.007, ηp2 = 0.005), higher fruit intake among boys (p = 0.043, ηp2 = 0.003), and lower vegetable intake among girls (p < 0.001, ηp2 = 0.009). However, LTOPA was unrelated to the overall healthy eating index, candy intake, and the proportion of added sugar to total energy intake (p > 0.05). LTOPA was only associated with some healthy eating behaviours, and there is much room for improvement in the diets of Swedish adolescents.